The impact of police on criminal justice reform: evidence from Cincinnati, Ohio - Engel, Robin S. (Criminology & public policy, 2017)
Despite significant national reductions in crime during the past three decades, a comparable reduction in adult arrest rates has not occurred. In addition, scant attention has been paid to the role of the police in pretrial justice and other criminal justice reform efforts, despite their role as gatekeepers to the criminal justice system. A key inquiry that must be addressed by both academics and practitioners is whether it is possible to reduce crime and the number of arrests simultaneously. Cincinnati (Hamilton County), Ohio, provided a unique opportunity to examine this unanswered question when it closed the Queensgate Correctional Facility in 2008, thereby reducing the available jail space in the county by 36%. By relying on an interrupted time‐series analysis, our findings show that contrary to public concern, both crime and arrests were reduced in Cincinnati even after the jail closure. Specifically, the Cincinnati Police Department reported a statistically significant decrease in felony arrests, and a nonsignificant decline in misdemeanor arrests, while maintaining a continued (nonsignificant) decline in violence and property crimes. Importantly, our findings demonstrate that the previous existent downward trend in Cincinnati reported crimes was not interrupted with the loss of more than one third of the available jail space in Hamilton County.